Pengaruh Suhu pada Inhibitor Daun Pandan Terhadap Laju Korosi pada Baja SS-304 dalam Larutan Asam HCL 0,1M - Laras Andria Wardani; Hernowo Widodo; Lisa Adhani; Everlita Sabrina; Amaliah Annisa (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2021)
The phenomenon of corrosion cannot be avoided in the use of the metal industry, therefore a corrosion inhibitor is needed to inhibit the corrosion rate of steel. The aim of this research is to obtain natural inhibitors that are effective in inhibiting the corrosion rate. In this study, the sample used is stainless steel which is most often used in everyday life, namely SS (Stainless Steel)-304. Some of the organic or natural inhibitors used in this study is pandan leaves. The variables used were immersion time and temperature. Furthermore, the parameters studied were the corrosion rate of steel and the morphology of SS-304 steel using the SEM test. The results showed that the best corrosion rate and morphology using pandan leaves at a temperature of 60â„ƒ soaked with 0,1 N HCL solution for 5 weeks.